The Influence Of Direct Marketing And Personal Selling On Customer Retention Of L.300 FD Cars (Case Study At PT. Lautan Berlian Utama Motor Lahat) - Oktaria, Isdwiyanti; Rusilawati , Tri; Amaludin, Amaludin (Journal of Management, Economic, and Accounting, 2025)
This study aims to determine how Direct Marketing and Personal Selling partially and simultaneously influence Customer Retention of the L.300 FD car (Case Study at PT. Lautan Berlian Utama Motor Lahat). The sample in this study was 60 respondents. The sampling method used by the researcher was Incidental Sampling. This type of research is quantitative research using multiple linear regression analysis techniques processed using the SPSS application and produces a regression equation Y = 4.546 + 0.634 X1 + 0.254 X2. The results of this study obtained Direct Marketing and Personal Selling have a significant partial effect on Customer Retention of the L.300 FD car (Case Study at PT. Lautan Berlian Utama Motor Lahat). Direct Marketing and Personal Selling have a significant simultaneous effect on Customer Retention of the L.300 FD car (Case Study at PT. Lautan Berlian Utama Motor Lahat).